Hybridizing electron-mediated H5PMo10V2O40 with CdS/g-C3N4 for efficient photocatalytic performance of Z-scheme heterojunction in wastewater treatment. (October 2022) - Liang, Chong; Cui, Mingyu; Zhao, Wei; Dong, Linyang; Ma, Shangshang; Liu, Xutang; Wang, Dingkai; Jiang, Zhijie; Wang, Fei
Abstract: Photocatalytic technology has been considered as a promising method to alleviate environmental pollution owing to the dual characteristics of redox. The novel V-based H5 PMo10 V2 O40 (HPA-2) photocatalyst with Z-scheme heterostructure was constructed. The energy level of HPA-2 matches well with CdS and g-C3 N4 (CN) according to Mott-Schottky and UV–Vis diffused reflectance tests, which allows the efficient separation of photogenerated electrons. The optimized CdS/HPA-2/CN showed superior ability in Rhodamine B (RhB) degradation and reduction of Cr (Ⅵ) under visible light irradiation. The maximum rate constant reached 0.092 min −1 for RhB degradation at 60 min and 0.260 min −1 for Cr (Ⅵ) reduction at 20 min, respectively. The photocatalytic mechanism was analyzed by adding scavengers. The effect of active species for RhB degradation was determined as h +  > ·O2 −  > ·OH, while ·O2 − and e − were essential for the reduction of Cr (Ⅵ). Besides, cyclic tests exhibit excellent repeatability and stable structure of CdS/HPA-2/CN after four cycles. Meanwhile, the detailed degradation process of RhB involving de-ethylation, hydroxylation, substitution and decarboxylation was determined according to LC-MS and evaluated by Fukui function calculation. Furthermore, total organic carbon content decreased to 6.2% of the initial value. In this work, as an electron mediator, HPA-2 provides the inspiration for construction of Z-scheme heterojunction, and CdS/HPA-2/CN exhibits enormous potential in the environmental remediation by photocatalysis. Graphical abstract: Image 1 Highlights: A novel CdS/HPA-2/CN photocatalyst with Z-scheme heterostructure was constructed. As electron mediator, HPA-2 provides an inspiration for construction of Z-scheme heterojunction. The CdS/HPA-2/CN showed enhanced performance in environmental remediation. The possible and detailed degradation process of RhB was proposed.